MULTICRITERIA OPTIMIZATION PROBLEM STATEMENT IN ELECTRIC POWER INDUSTRY - Churina, O. Y. (Electronics and Control Systems, 2018)
In this paper, optimization problems of the electric power industry, modeled on the basis of nonstationary nonlinear systems, are considered. The analysis of admissible solutions of the optimization problem is performed on the basis of the composition of subsets of coordinated and compromise solutions. At the same time, the change in the objective functional of the optimization problem is due to variations in the states of the environment without changing the system of constraints that determine the set of admissible values of the controlled variables. It is proposed to take into account the nonlinearity and discreteness of optimization problems in the process of modeling electric power systems.